Inhaled aerosolised prostacyclin as a selective pulmonary vasodilator - Van Heerden, Peter Vernon (My University, 2014)
This thesis examines the premise that inhaled aerosolised prostacyclin (IAP) is a safe and efficacious agent for use as a selective pulmonary vasodilator (SPV) in patients with severe acute respiratory distress syndrome (ARDS). initially, three tests of nebuliser function were undertaken to support the use of this device for the delivery of aerosols in subsequent studies described in this thesis. The findings were - both jet nebuliser brands (MistyNeb and Sidestream) used in the studies described in this thesis produced a large proportion (approximately 50 - 80%) of aerosolised particles in the respirable range ( 1 - 5 microns). The Sidestream device was the more efficient of the two tested, aerosolised particles were deposited widely within the lung of a test subject as assessed by ventilation scan and - the maximum rate of nebulisation by the Sidestream jet nebuliser was less than 15 ml/hr. Next, a pilot study using nitric oxide (NO) 10 parts per million (ppm) and IAP 50 nanograms per kilogram per minute (ng/kg/min) was done, comparing the two agents as SPV’s in five patients with hypoxaemia secondary to ARDS. Neither SPV resulted in systemic haemodynamic changes, indicating true pulmonary selectivity. IAP improved oxygenation to a degree comparable to NO as measured by the ratio of arterial partial pressure of oxygen to inspired oxygen concentration (PaOg/FiOg), shunt fraction and alveolar to arterial ox’ gen difference or gradient (A-aDOg). Neither agent had a significant effect on mean pulmonary artery pressure (MPAP). Thereafter pigs (mass up to 25 kg) were exposed to aerosolised normal saline, the control group (C group), aerosolised alkaline glycine diluent (D group) or IAP in a concentration of 10 micrograms/millilitre in glycine buffer (P group) for up to 8 hours. Pigs in the D and P groups developed mild acute sterile tracheitis, involving the superficial layers of the trachea (shown histologically and ultrastructuraily). The D group also showed inflammatory changes in the bronchioles. These findings suggest caution in the use of high volumes of aersolised alkaline glycine diluent during IAP therapy. A study was then carried out to determine the efficacy of and dose-response relationships to IAP, when used as a SPV in patients with severe hypoxaemia due to the ARDS. This was an unblinded interventional prospective clinical study in a university tertiary referral centre, general intensive care unit. Nine adult patients with severe ARDS (as defined by a lung injury score > 2.5) were enrolled. All patients received IAP over the dose range 0 to 50 ng/kg/rnin. The IAP was delivered via a jet nebuliser placed in the ventilator circuit. Dose increments were 10 ng/kg/min every 30 min. Cardiovascular parameters, indices of oxygenation and shunt fraction were measured or calculated at each dose interval, as were platelet aggregation and systemic levels of prostacyclin metabolite. A generalised linear regression model was used to determine a dose effect of IAP on the measured parameters. Wilcoxon ranked sums test for related measures was used to compare the effects of various doses of IAP. LAP acted as a SPV, with a statistically significant dose-related improvement in PaOg/FiOg (p = 0.003) and A-aDOg (p = 0.01). Systemic prostacyclin metabolite levels increased significantly with delivered IAP dose (p = 0.001). There was no significant dose effect on systemic or pulmonary arterial pressures, nor on platelet function, as determined by platelet aggregation in response to challenge with adenosine diphosphate. The findings indicated that IAP is an efficacious SPV, with marked dose-related improvement in oxygenation and with no demonstrable effect on systemic arterial pressures over the dose range 0 - 5 0 ng/kg/min. Despite significant systemic levels of prostacyclin metabolite, there was no demonstrable platelet function defect. In order to further clarify the possible antiplatelet effect of systemic prostacyclin metabolites observed during IAP therapy, an in vitro study was performed. Platelet aggregation in response to adenosine diphosphate (ADP) and collagen, as well as measurement of the maximum amplitude by thrombelastography, was undertaken in vitro using venous blood from eight healthy subjects exposed to extremely low concentrations of prostacyclin (0,10,100 and 500 pg/ml). A significant anti-platelet effect was demonstrated.